'In uijterste Deftigheijt en Perfectie'. Oude kunst en historische archieven in monumentaal Occo Hofje te Amsterdam (Bulletin KNOB, 1992)
The Almshouse of Occo at Amsterdam is a charitable institution, which has been founded in the 18th century. The institution was established from the legacy of the rich Roman Catholic businesswoman Cornelia Elisabeth Occo. She desired that after her death a building of charity would be built to lodge 33 poor, Roman Catholic widows or unattached women of 50 years and older gratuitously, with medical care included.The first foundation stone laying of the, at the time relative luxurious, building (mostly private rooms) took place in 1774. Four years later the first inhabitants moved into their houses Architect Jan Luyten designed a stately but sober building in a symmetrical Louis XVI-style, which linked up very well with the, at the time in Amsterdam also very popular, neo-classicist tendency. In 1977-1978 the exterior of this important monument has been restored completely and in 1990-1991 the interior was renovated and adapted to the demands of the time.Thus the almshouse can still function the way it was meant by Cornelia Elisabeth Occo in the 19th century. Traditionally an almshouse in Amsterdam also has the disposal of a governors room, where the board of the almshouse can meet regularly. Most of the time these rooms were richly adorned with paintings and works of art. In the Almshouse of Occo the walls of this room were completely hanged with beautiful paintings from the 16th to the 18th century, most of the portraits of the family Occo and of their later hereditaries, the family Gilles de Pélichy.The almshouse also possesses historical archives with private and business-like records of the foundress and her family and the records of the almshouse and the governors. These archives now have been described and made an inventory of and with that they represent an important source for the socio-economical history of Amsterdam.